Dampak penambahan limbah biomassa cangkang kelapa sawit sebagai bahan bakar boiler terhadap heat rate dengan metode co-firing - Nefri Yurisman; Rafil Arizona (Jurnal Teknik Mesin Indonesia, 2022)
Indonesia's electricity plants mostly use off-renewable resources to meet the electricity needs of people or industries such as coal. This crisis problem requires that we seek a fuel alternative to replace coal or at least reduce coal consumption. One of them biomass fuel by applying co-firing methods. The co-firing process aims to raise thermal energy in the boilers, and therefore it is expected to raise the heat rate of the boiler fuel. The application of research uses a comparative analysis method that will compare heat rate using co-firing method with heat rate without the co-firing method. Analysis shows the impact of adding biomass waste as a boiler fuel to create a heat rate with co-firing increased by 19810.41 kkal/kWh compared to the time without co-firing 19207.08 kkal/kWh. The test also affected its carbon content of 57.62% increased 57.88%, while in total sulfur from 0.20% to lower by 0.19%.